Influence of escaping of Na & K on physical properties in lead-free Na0.92K0.08NbO3 ceramic. (26th October 2019) - Kathait, Gambheer Singh; Thapliyal, Prashant; Biswas, Don; Rohilla, Vishal; Singh, Surendra
Abstract: Lead-free Na x K1– x NbO3 (NKN) ceramic with x = 0.08 was prepared by a conventional solid-state reaction method to investigate the influence of the Escaping of Na & K on their physical properties. It has been found that the NKN ceramics with x = 0.08 exhibit pure perovskite (ABO3 ) structure. The pure phase NKN was achieved for all sintering temperatures of 1100 °C, 1150 °C, 1200 °C and 1250 °C. Change in microstructure, indicates that the grain size increases with the increasing sintering temperatures. The dielectric constant was dependent of the Escaping of Na & K. From the analyses, we suggest that the high dielectric constant for the NKN ceramics near sintering temperature 1150 °C are closely related to their low escaping of Na & K and microstructures of uniformly distributed large grains rather than the widely believed morphotropic phase boundary effect of lattice parameter discontinuity.